1999
DOI: 10.1021/es980715q
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Nickel and Copper to Fish Gills Predicts Toxicity When Water Hardness Varies, But Free-Ion Activity Does Not

Abstract: Based on a biotic-ligand model (BLM), we hypothesized that the concentration of a transition metal bound to fish gills ([M gill ]) will be a constant predictor of mortality, whereas a free-ion activity model is generally interpreted to imply that the chemical activity of the aquo ("free") ion of the metal will be a constant predictor of mortality. In laboratory tests, measured [Ni gill ] and calculated [Cu gill ] were constant predictors of acute toxicity of Ni and Cu to fathead minnows (Pimephales promelas) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(110 citation statements)
references
References 12 publications
7
100
0
3
Order By: Relevance
“…Concentration of extracellular Cu is probably a better indicator because it does not need to consider the matrix effects in aqueous phase. Meyer et al (1999) used fathead minnows (Pimephales promelas ) to evaluate Cu toxicity and found that concentration of Cu bounded on fish gill ([Cu gill ]) was constant predictors of toxicity when the Ca concentration increases, whereas the free-ion activities of Cu are not constant predictors of toxicity. Di Toro (2001) used larval fathead minnow to observe the effect of variations in DOC concentration on LC 50 of Cu and found that the gill Cu concentration can be used to predict acute mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Concentration of extracellular Cu is probably a better indicator because it does not need to consider the matrix effects in aqueous phase. Meyer et al (1999) used fathead minnows (Pimephales promelas ) to evaluate Cu toxicity and found that concentration of Cu bounded on fish gill ([Cu gill ]) was constant predictors of toxicity when the Ca concentration increases, whereas the free-ion activities of Cu are not constant predictors of toxicity. Di Toro (2001) used larval fathead minnow to observe the effect of variations in DOC concentration on LC 50 of Cu and found that the gill Cu concentration can be used to predict acute mortality.…”
Section: Resultsmentioning
confidence: 99%
“…[103] For copper, cadmium, and nickel, a strong relationship has been observed between metal accumulation on the gills of rainbow trout or fathead minnows and that predicted using acute toxicity data. [31,40,57,131] Furthermore, physiologically based log K values (log K Ag-gill ATPase = 7.6) have been shown to be useful for predicting the silver binding to specific toxic sites of the gills of rainbow trout. [132] Future research will most certainly need to move beyond total body burdens and total bioaccumulation.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…These values were derived from the available literature at the time, but it is likely that consideration of more recent studies would result in significantly different values. Furthermore, enough data now may be available to derive at least a hardness-based criterion, if not even a criterion that considers the complexation of Al to biological surfaces such as fish gills (i.e., Meyer, 1999;Meyer et al, 1999).…”
Section: F Future Recommendationsmentioning
confidence: 99%